The Continuous Concentration of Particles and Cancer Cell Line Using Cell Margination in a Groove-Based Channel - Sheng Yan; Dan Yuan; Qianbin Zhao; Jun Zhang; Weihua Li (Micromachines, 2017)
In the capillary venules, blood cells auto-separate with red blood cells aggregating near the centre of vessel and the nucleated cells marginating toward the wall of vessel. In this experiment, we used cell margination to help enrich the Jurkat cells via a groove-based channel which provides a vertical expansion-contraction structure, wherein the red blood cells invade the grooves and push the Jurkat cells to the bottom of the channel. The secondary flows induced by the anisotropic grooves bring the Jurkat cells to the right sidewall. Rigid, 13-µm diameter polystyrene particles were spiked into the whole blood to verify the operating principle under various working conditions, and then tests were carried out using Jurkat cells (~15 µm). The performance of this device was quantified by analysing the cell distribution in a transverse direction at the outlet, and then measuring the cell concentration from the corresponding outlets. The results indicate that Jurkat cells were enriched by 22.3-fold with a recovery rate of 83.4%, thus proving that this microfluidic platform provides a gentle and passive way to isolate intact and viable Jurkat cells.